Design And Fabrication Of Moulds Using Additive Manufacturing For Producing Silicone Rubber Products - Brandan, Hendrick Jampong; Othman, Mohd Hilmi (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This study focuses on the design and fabrication of moulds using additive manufacturing techniques for producing silicone rubber products. Additive manufacturing, also known as 3D printing, offers several advantages in mould production, such as increased design flexibility, reduced lead times, and costeffectiveness. The research aims to investigate the feasibility and effectiveness of utilizing additive manufacturing methods for mould fabrication in the context of silicone rubber product manufacturing. The study includes the design phase, where moulds are created using computer-aided design (CAD) software, and the fabrication phase, where the moulds are produced using additive manufacturing techniques. Various factors are considered during the mould design process, including the geometry of the silicone rubber product, the desired surface finish, and the appropriate runner and gate configurations to minimize air entrapment and bubble formation. The moulds are then fabricated using additive manufacturing methods, specifically tailored to silicone rubber materials.The performance and quality of the moulds are evaluated through physical testing and comparison with traditional mould fabrication methods. Parameters such as mould accuracy, dimensional stability, and surface finish of the sample are analyzed to assess the effectiveness of additive manufacturing in producing high-quality silicone rubber products. The results demonstrate the feasibility and potential of additive manufacturing for mould fabrication in silicone rubber product manufacturing. The advantages of this approach include the ability to create complex geometries, optimize mould design for minimal air entrapment, and reduce lead times for mould production. The study also identifies areas for further improvement and optimization of the additive manufacturing process in the context of silicone rubber product manufacturing.